Architecture and Design of Oracle Scheduler. Issue 1 (January 2021) - Liu, Jimin
Abstract: Oracle scheduler focuses on the automatic management, maintenance and monitoring of Oracle database jobs. Through it, many routine database tasks can be automatically executed, and human intervention can be reduced, so as to improve the efficiency of system operation and implement more flexible and complex task management. This paper introduces the concept and classification of Oracle scheduler, analyzes each component of Oracle scheduler, explains its overall architecture and tasks of different components, summarizes the problems needing attention in design according to design experience, and illustrates its application through the creation of Oracle scheduler object instance, job scheduling and evaluation of execution frequency.